Pembelajaran Tauhid Pada Anak Usia Dini (Studi Tentang Formulasi dan Strategi Pembelajaran) - Laila Wardati; OK. M. Daniel Syahindra; Leni Masnidar Nasution (UMSU, 2019)
This study aims to (1) Determine the formulation of early childhood tauhid learning materials in TK Rusyda Medan, (2) To find out the strategies used in early childhood learning in TK Rusyda Medan. The method used in this study is a qualitative method with a descriptive analysis approach. The results showed that in TK Rusyda Tauhid learning was carried out with a number of material formulations namely about the introduction of Allah, about the introduction of the religion they professed, about the consequences of a Muslim who is associated with piety and good social behavior, around Islamic symbols either in the form of images or in the form of Islamic songs. The several methods used are exemplary methods, habituation methods, singing methods, story methods, stories, advice methods.